2021
DOI: 10.5603/cj.a2019.0065
|View full text |Cite
|
Sign up to set email alerts
|

Could autonomic nervous system parameters be still helpful in identifying patients with left ventricular systolic dysfunction at the highest risk of all-cause mortality?

Abstract: Background: Autonomic imbalance is associated with poor prognosis of patients with systolic dysfunction. Most of the previous data were written several years ago and constituted to cardiovascular or arrhythmic mortality. The current treatment of these patients has improved substantially over the last decades, and thus, the population at risk of death may have altered as well. Consequently, data on high-risk patients with systolic dysfunction in the modern era are sparse and those from previous trials may no lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In the present study, it was shown in both uniand multivariate Cox analyses, the role of BRS in the prediction of MACE occurrence in patients with HF of ischemic origin and LVEF up to 50%. The pre-specified cut-off value for BRS (3 ms/mmHg) is consistent with the results acquired by other researchers, where BRS was determined by both invasive and non-invasive methods [3,4,19,27,28,47]. In the current study, patients with BRS below 3 ms/mmHg had a relative risk for MACE threefold higher than patients above the cut-off.…”
Section: Prognostic Value Of Ans Indices In the Identification Of Macesupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, it was shown in both uniand multivariate Cox analyses, the role of BRS in the prediction of MACE occurrence in patients with HF of ischemic origin and LVEF up to 50%. The pre-specified cut-off value for BRS (3 ms/mmHg) is consistent with the results acquired by other researchers, where BRS was determined by both invasive and non-invasive methods [3,4,19,27,28,47]. In the current study, patients with BRS below 3 ms/mmHg had a relative risk for MACE threefold higher than patients above the cut-off.…”
Section: Prognostic Value Of Ans Indices In the Identification Of Macesupporting
confidence: 90%
“…Previous investigations concerning MACE risk assessment among patients with coronary artery disease were dedicated to other well-known clinical parameters [ 25 , 26 ], which were also confirmed in the present study. The role of ANS indices and MTWA was previously proven for arrhythmic, cardiac and all-cause mortality [ 2 – 7 , 19 , 27 34 ], however not for MACE, which are common and relevant in this population [ 1 ]. Moreover, the vast majority of cited studies omitted patients with ejection fraction 40–50%, who have similarly poor prognosis [ 35 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation